2017
DOI: 10.1177/1948550617742192
|View full text |Cite
|
Sign up to set email alerts
|

How Discrimination Shapes Social Identification Processes and Well-Being Among Arab Americans

Abstract: The increasingly xenophobic U.S. climate warrants a close investigation of Arab American responses to discrimination. We conducted secondary analyses of two large data sets to examine social identity processes and their relationship to well-being. In a representative sample of Muslim Arab Americans (Study 1, n = 228), discrimination was related to decreased American identification, which in turn predicted lower well-being. Another large sample of Arab Americans (Study 2, n = 1,001) revealed how social identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Badea et al (2011) found evidence for negative associations between PMB's negative contact experiences with the majority group and identification with the majority group as well as between negative contact experiences with the minority group and identification with the minority group. There is further empirical support for this mechanism in the immigration context regarding the negative association between negative majority group contact (i.e., rejection or discrimination) and identification with the majority group (e.g., Bobowik, Martinovic, Basabe, Barsties, & Wachter, 2017;Hakim, Molina, & Branscombe, 2018;Jasinskaja-Lahti et al, 2009;Verkuyten & Yildiz, 2007;Wiley, Lawrence, Figueroa, & Percontino, 2013). Also, Wiley (2013) found support for this mechanism regarding negative contact experiences (i.e., rejection) with the minority group and minority group identification.…”
Section: The Relation Between Contact and Identification With Majoritmentioning
confidence: 81%
See 4 more Smart Citations
“…Badea et al (2011) found evidence for negative associations between PMB's negative contact experiences with the majority group and identification with the majority group as well as between negative contact experiences with the minority group and identification with the minority group. There is further empirical support for this mechanism in the immigration context regarding the negative association between negative majority group contact (i.e., rejection or discrimination) and identification with the majority group (e.g., Bobowik, Martinovic, Basabe, Barsties, & Wachter, 2017;Hakim, Molina, & Branscombe, 2018;Jasinskaja-Lahti et al, 2009;Verkuyten & Yildiz, 2007;Wiley, Lawrence, Figueroa, & Percontino, 2013). Also, Wiley (2013) found support for this mechanism regarding negative contact experiences (i.e., rejection) with the minority group and minority group identification.…”
Section: The Relation Between Contact and Identification With Majoritmentioning
confidence: 81%
“…Accordingly, our results would imply a stronger focus on effects of specific aspects of positive contact on majority group identification and cultural adoption as few existing studies already do, for example perceived acceptance of PMB by the majority society (Te Lindert et al, 2008) or intergroup friendships (de Vroome et al, 2011;Sabatier, 2008). Previous acculturation research focused mostly on the negative effects of negative majority group contact on identification with the majority group and acculturation (e.g., Badea et al, 2011;Berry & Hou, 2017;Bobowik et al, 2017;Hakim et al, 2018;Jasinskaja-Lahti et al, 2009;Ramos, Cassidy, Reicher, & Haslam, 2016;Verkuyten & Yildiz, 2007).…”
Section: Theoretical Implicationsmentioning
confidence: 82%
See 3 more Smart Citations